Community Group-Based Tourism Development Model: Banten Lama Tourism Area - Rakhmat Jazuli; Nurikah Nurikah (Universitas Kuningan, 2021)
Tourism development in Banten Lama area has highly made significant progress after the Banten Provincial Government revitalized Banten Lama area with a budget of 80 billion in 2018 and 20 billion in 2019. This development was not only focused on revitalization, but involved many parties. The purpose of this research is to find how is the role of local government as a regulator in the development of community-based tourism in the Banten Lama Tourism area? and how is the community group-based tourism development model in Banten Lama Tourism Area? This study employed an empirical juridical method based on a qualitative data approach. The data sources were taken from primary data collected through interviews and field research at relevant government agencies. For example, the tourism office, tourism awareness groups, tourism business actors, and communities related to tourism development in the Banten Lama area. These are analyzed and served as the findings. The findings revealed the Banten Provincial Government and the Serang City Government, the regulators of tourism development in the Banten Lama area, have a role in the carrying capacity of policies and budgets in revitalizing the Banten Lama area into leading tourism. This is stated in the Banten Province tourism development plan and has started from 2018 and 2019. The synergy of local governments with community group-based tourism development is based on the following groups: community groups who are members of tourism development groups known as tourism awareness groups, community groups who are members of community groups originating from religious elements around Banten Lama tourism area, and community groups who are members of business groups tourism. The existence of these community group must become social capital for the Banten Provincial Government and Serang City Government in preparing regulations for tourism development in the Banten Lama area as a leading destination.Pengembangan pariwisata dikawasan Banten Lama mengalami kemajuan yang sangat signifikan setelah Pemerintah Propinsi Banten melakukan revitalisasi kawasan Banten Lama dengan anggaran 80 milyar ditahun 2018 dan 20 milyar di tahun 2019, pengembangan ini tidak hanya terfokus pada revitalisasi, tetapi banyak melibatkan berbagai pihak dimasyarakat. Tujuan penelitian untuk mengetahui bagaimana peran pemerintah daerah sebagai Regulator dalam pengembangan pariwisata berbasis kelompok masyarakat Di kawasan Wisata Banten Lama ? dan bagaimana model pengembangan pariwisata berbasis kelompok masyarakat di Kawasan Wisata Banten Lama ? Metode yang digunakan dalam penelitian ini adalah metode yuridis empiris berdasarkan pendekatan data kualitatif yang bersumber dari data primer melalui wawancara dan penelitian lapangan pada instansi pemerintah terkait yaitu dinas pariwisata, kelompok sadar wisata, dan pelaku usaha pariwista serta masyarakat yang terkait dengan pengembangan pariwisata dikawasan Banten lama sebagi sumber data penelitian untuk dianalisis dan menjadi hasil pemebehasan dalam penelitian. Hasil penelitian yaitu Pemerintah Propinsi Banten dan Pemerintah Kota serang sebagai regulator pengembangan pariwisata dikawasan Banten Lama memiliki peran dalam daya dukung kebijakan serta anggaran dalam revitalisasi kawasan Banten Lama menjadi wisata unggulan hal ini teruang dalam rencana pengembangan pariwisata Propinsi Banten dan dimulai dari Tahun 2018 dan 2019, sinergitas pemerintah daerah dengan pengembangan pariwisata berbasis kelompok masyarakat didasarkan pada kelompok masyarakat yang tergabung dalam kelompok pengembangan pariwisata yang dikenal dengan kelompok sadar wisata, kelompok masysrakat yang tergabung dalam kelompok masyarakat yang berasal dari unsur keagamaan disekitar wisata Banten Lama dan kelompok masyarakat yang tergabung dalam kelompok usaha pariwisata. Adanya unsur keterlibatan kelompok masyarakat ini harus menjadi modal sosial oleh pemerintah Propinsi Banten dan Pemerintah Kota Serang dalam menyusun regulasi untuk